(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study investigates the impact of geographic dispersion on supply chain resilience and robustness, focusing on the mediating role of responsiveness. Employing a deductive and quantitative approach, data were collected through an online survey administered in November 2024 to 98 employees across eleven key sectors in Saudi Arabia, including Consumer Goods, Food and Beverages, Banking, and others, representing a 100% response rate and encompassing various company sizes. Established scales were adapted to measure geographic dispersion, resilience (based on Pettit, Croxton, and Fiksel’s work), robustness, and responsiveness. Statistical methods, including correlation and regression analysis, were utilized to test the hypothesized relationships. The findings show that geographic dispersion has a positive but limited effect on resilience (H1) and a marginally significant effect on robustness (H2). Responsiveness strongly mediates the relationship with resilience (H3), but its mediating effect on robustness is weak and not statistically significant (H4). The study recommends that managers prioritize investments in enhancing supply chain responsiveness through advanced information systems, flexible logistics, and strong stakeholder relationships to counteract the challenges posed by geographic dispersion and ensure supply chain stability and adaptability, particularly within the Saudi Arabian business context.